EFFECTIVENESS OF DOUBLE-GLOVING METHOD ON PREVENTION OF SURGICAL GLOVE PERFORATIONS AND BLOOD CONTAMINATION: A PROSPECTIVE STUDY - H Chavda, Divyang; Mudgal, Manish (Asian Journal of Pharmaceutical and Clinical Research, 2024)
Objectives: To evaluate efficacy of double gloving to provide mechanical barrier against communicable diseases and also to evaluate different parameters affecting glove perforation rate. Methods: This prospective study was performed in department of General Surgery at tertiary care teaching hospital of Gujarat. This study involved a group of surgeons and operation theatre nursing staff. Randomization of the participants was done with the closed envelope method in two groups: single gloving and double gloving. Glove perforation rate and hand contamination rate was calculated and compared between both the groups. Participants of double gloving groups were also asked for discomfort using double gloves and compromised tactile sensations. Results: There was no statistically significant difference in the glove perforation rate between single gloves and double outer gloves. (p=0.55) But, the glove perforation rate was significantly low in double inner gloves than single gloves. (p=0.004) The hand contamination rate was significantly lower amongst perforated double gloves than perforated single gloves. (p=0.00001) Awareness of glove perforation was absent in majority of the participants in both the groups. All the participants in the double gloving group were comfortable with using double gloves and their tactile sensations were not compromised. Conclusion: This study concluded that double gloving efficiently prevented hand contaminations during a surgery. There was no significant difference noted in glove perforation rates in both single and double gloving groups. Double gloving is recommended for the surgeons and nursing staff to protect them from blood borne infections and eliminate the chances of surgical site infections in the patients.